FROM SYMBOLIC BREAKTHROUGH TO TECHNOCRATIC AUTHORITY: MEDIA FRAMING OF SHERLY TJOANDA’S LEADERSHIP IN REGIONAL ONLINE NEWS COVERAGE - Hi. Amin, Julaiha (International Journal of Multidisciplinary Reseach, 2026)
This study examines how regional online media construct the legitimacy of female political leadership in a decentralized democracy. Focusing on the early months of Sherly Tjoanda’s tenure as the first female Governor of North Maluku, the research investigates whether media framing remains confined to symbolic gender representation or evolves toward technocratic authority. Using a qualitative framing analysis based on Pan and Kosicki’s structural model, this study analyzes four news articles published by Nuansamalut.com during the first three months following the governor’s inauguration (February–May 2025). The analysis examines syntactic, script, thematic, and rhetorical structures to identify patterns of meaning construction and longitudinal shifts in framing. The findings reveal a sequential transformation of media framing. The initial coverage emphasizes symbolic breakthrough and gender milestone narratives. Subsequent reporting shifts toward managerial rationality (100-day programs), executive performance (hospital upgrading initiatives), and moral-administrative governance (budget accountability enforcement). Rather than maintaining a gendered emotional frame, the media progressively constructs technocratic legitimacy. This indicates that regional media in decentralized contexts can function as agents of legitimacy consolidation rather than perpetuators of gender stereotypes. This study introduces the concept of sequential framing of legitimacy, highlighting the temporal evolution of media framing from symbolic to rational-legal authority. By situating the analysis at the subnational level, the research expands gendered political framing literature beyond national election campaigns and Western contexts. The findings contribute to communication and political legitimacy scholarship by demonstrating how media discourse mediates the transformation of symbolic representation into technocratic governance authority in emerging democracies.